GOOD LIVING AS AN ALTERNATIVE TO DEVELOPMENT AND AS A RESPONSE TO THE MEGACRISIS - ARCE-ROJAS, Rodrigo (2024)
This article deals with the concept of Good Living as one of the most visible expressions of alternatives to development and how its postulates and practices can contribute to responses to the planetary megacrisis. For this purpose, a reflection based on a specialized bibliographical review is carried out, and is complemented by a surves. From the reflection it is concluded that although the concept of Good Living is under construction, as an alternative ethical-political proposal, it constitutes a semantic, discursive and mobilizing force of multiple possibilities, applicable to a diversity of contexts, as it recovers central values to respond to the planetary mega-crisis from basic principles of recovery of harmony among people, social harmony and harmony between human beings and nature, the ontological turn from individualism to conviviality, from the ideology of domination of people, bodies, ideas and nature, to the ethics of recursive relationality in which the rights of nature make sense as we ourselves recognize ourselves as nature within the framework of an ontology of continuity. This implies removing and transforming the core of the colonialist, patriarchal and speciesist neoliberal capitalist system. Although the concept has the strength of being open to multiple strands that share contributions to alternatives to development, it is also its weakness in exposing itself to political manipulation as has already happened in the countries that called for it. Hence the importance of the construction of the conceptual core that gives it personality without losing degrees of freedom and its transforming essence born from the original peoples.